Corporate Governance, Tax Avoidance, and Firm Value - Wawan Cahyo Nugroho; Dian Agustia (AFEBI Accounting Review, 2017)
This study aims to examine: (1) the influence of institutional ownership, independent commissioners on tax avoidance on firm value (2) the influence of tax avoidance on firm value (3) the influence of institutional ownership, independent commissioner to firm value mediated by tax avoidance. The population of this study are manufacturing companies listed on the Indonesian Stock Exchange for the study from 2013-2016. This study purposive sampling and arrived at 92 firms, using path analysis technique. The results of this study indicates that (1) institutional ownership significantly influence tax avoidance (2) independent commissioners have no influence on tax avoidance; (3) institutional ownership does not influence the firm value; (4) independent commissioner and tax avoidance have significant effect to firm value; (5) tax avoidance does not mediate the institutional ownership relationship to firm value. Keywords: Executive Incentives, Firm Value, Independent Commissioners, Institutional Ownership, Profitability, and Tax Avoidance